2015
DOI: 10.1063/1.4929281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nickel oxide nanoparticles on dielectric and optical properties of nematic liquid crystal

Abstract: Articles you may be interested inTunability of optical memory in ferroelectric liquid crystal containing polyvinylpyrrolidone capped Ni nanoparticles for low power and faster device operation Appl. Phys. Lett. 101, 074109 (2012) Corresposnding author, E-mail: jpsphysics@gmail.com, Tel: 0164-2864217 Abstract. In the present paper, we have studied the improvement in dielectric and optical properties of nematic liquid crystal (NLC) by doping of nickel oxide (NiO) nanoparticles. We have observed the dielectric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The study of dielectric and electro-optical properties of dispersed systems obtained by the dispersion of magnetic NPs (MNPs) into nematic LCs has been found to be very interesting [18][19][20]. Godovinova et al [18] measured the T NI of nematic LC 6CHBT dispersed with spherical or calamitic MNPs and found that the ferronematics dispersed with rod-like MNPs have higher T NI than the host nematic or ferronematics containing NPs of spherical shape.…”
Section: Citation Of Work Donementioning
confidence: 99%
See 1 more Smart Citation
“…The study of dielectric and electro-optical properties of dispersed systems obtained by the dispersion of magnetic NPs (MNPs) into nematic LCs has been found to be very interesting [18][19][20]. Godovinova et al [18] measured the T NI of nematic LC 6CHBT dispersed with spherical or calamitic MNPs and found that the ferronematics dispersed with rod-like MNPs have higher T NI than the host nematic or ferronematics containing NPs of spherical shape.…”
Section: Citation Of Work Donementioning
confidence: 99%
“…Large increase in the dielectric properties have been observed on increasing the NPs concentration from 1 to 10 wt%. Jamwalet al [20] studied the effect of nickel oxide (NiO) NPs on the dielectric and electro-optical properties of nematic LC 5CB and observed that due to the presence of NiO NPs the values of dielectric permittivity (ε ), dielectric loss (ε") and tan δ are decreased whereas the optical contrast has improved. The decrease of tan δ shows the low relaxation frequency of the ions.…”
Section: Citation Of Work Donementioning
confidence: 99%
“…The impact of LC on modern technology such as a biosensor, memory devices, LC-based lasers, holography has been profound [8,9]. Besides these modern familiar applications, there are other devices with improved properties of LC by doping nanoparticles or mixing with other inorganic/organic solvents as LCs are favorable material for the effective transfer of ions and electrons [6,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to above, reduction in crystal size would significantly increase the sensor performance and the band gap engineering by possible modification of MON which is one of the most exciting research area. Therefore, by altering these characteristics, the structural, sensing, optical and chemical properties of MON may be tuned and adapted to their potential to facilitate both fundamental research and practical applications through their advantageous chemical and physical properties [43][44][45][46][47][48][49][50] . Their novel properties can be tailored significantly by producing them at nanoscale in different morphologies.…”
Section: Introductionmentioning
confidence: 99%